(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study investigates the impact of multimodal literacy practices on students’ academic writing development in an EFL higher education context. Drawing on contemporary multimodality frameworks (New London Group, 2021; Serafini, 2022; Jewitt & Kress, 2023), this research explores how students engage with linguistic, visual, spatial, and digital resources when composing texts. A qualitative case study was conducted with undergraduate students at the University of Muhammadiyah Makassar. Data were collected through classroom observations, document analysis, and semi-structured interviews, followed by thematic analysis. The findings reveal that multimodal literacy significantly enhances students’ idea generation, structural clarity, audience awareness, and overall writing motivation. Students demonstrated an increased ability to integrate visual and textual elements coherently, which contributed to more engaging and conceptually accurate writing. However, the study also identifies challenges, including digital navigation constraints and cognitive overload. This article concludes with theoretical and pedagogical implications for strengthening multimodality-driven writing instruction in EFL settings.